Antiproliferative activities of several plant extracts from Turkey on rat brain tumor and human cervix carcinoma cell lines. Issue 1 (2nd January 2016) - Sahin Yaglıoglu, Ayse; Eser, Ferda; Tekin, Saban; Onal, Adem
Abstract : Turkey has a wide range of flora and fauna due to its climatic diversity. Medicinal plants from Turkey have been used since ancient times for their primary health care. In this study, we examined antiproliferative activities of the extracts from Crataegus monogyna, Vitis vinifera, Glycrrhiza glabra, Alnus glutinosa L. gaertn, and Alcea rosea against rat brain tumor (C6) and human cervical cancer (HeLa) cell lines. The results were compared with the standard anticancer drugs 5-Flurouracil (5-FU) and Cisplatin. C. monogyna, V. vinifera and A. rosea exhibited better antiproliferative activity than 5-FU and cisplatin at 100-75 µg/mL concentrations, against C6 cell lines. On the other hand, C. monogyna and V. vinifera extracts showed considerable antiproliferative activity against HeLa cells compared with 5-FU and cisplatin at 100-75 µg/mL. It can be suggested that, C. monogyna, A. glutinosa L. gaertn, V. vinifera and A. rosea extracts could be developed as an anticancer drug. GRAPHICAL ABSTRACT: